Natural and synthetic drugs and formulations for intravaginal HPV clearance - Nizar A. Khamjan; Saba Beigh; Abdullah Algaissi; Kanu Megha; Mohtashim Lohani; Majid Darraj; Nader Kamli; Faisal Madkhali; Sajad Ahmad Dar (Elsevier, 2023)
Background: Except for a few preventative Human Papillomavirus (HPV) vaccines, there is currently no cure for HPV infection. There are a number of cutting-edge strategies and potent medications or herbal formulations that can be applied topically for early clearance of HPV infection before HPV DNA gets integrated into host cell genome. This is facilitated due to cervical cancer having distinct and well-recognized long precancerous stages. Objectives: This review aims to outline every possible medication and formulation, both natural and synthetic, that can be applied topically as intravaginal application to help remove HPV infection at an early precancerous stage. Results: Several anti-HPV/HPV clearance compounds and formulations for high-grade lesions are undergoing clinical trials. However, the majority of compounds are still in the early stages of development and require additional research to become viable HPV clearance candidates. Synthetic drugs may be more promising because they may have a more targeted effect; however, they may also have significant adverse effects. On the other hand, natural medications are safer to use. They are less specific, but have minimal to no adverse effects. Conclusions: This article may serve as a valuable resource of information for managing and preventing precancerous carcinogenic HPV infections. Research could be directed toward developing candidate drugs to make evidence-based decisions about advancing them to clinical trials and, eventually, to the market for potential use in the prevention and control of cervical cancer, which is almost always preventable or even curable if detected early.